The Spontaneous Autoimmune Neuromyopathy in ICOSL−/− NOD Mice Is CD4+ T-Cell and Interferon-γ Dependent - Briet, Claire; Bourdenet, Gwladys; Rogner, Ute C.; Becourt, Chantal; Tardivel, Isabelle; Drouot, Laurent; Arnoult, Christophe; do Rego, Jean-Claude; Prevot, Nicolas; Massaad, Charbel; Boyer, Olivier; Boitard, Christian (Frontiers in Immunology, 2017)
Abrogation of ICOS/ICOS ligand (ICOSL) costimulation prevents the onset of diabetes in the NOD mouse but, remarkably, yields to the development of a spontaneous autoimmune neuromyopathy. At the pathological level, ICOSL-/-NOD mice show stronger protection from insulitis than their ICOS-/- counterparts. Also, the ICOSL-/-NOD model carries a limited C57BL/6 region containing the icosl nul mutation but, in contrast to ICOS-/-NOD mice, no gene variant previously reported as associated to NOD diabetes. Therefore, we aimed at providing a detailed characterization of the ICOSL-/-NOD model. The phenotype observed in ICOSL-/-NOD mice is globally similar to that observed in ICOS-/- and ICOS-/-ICOSL-/- double knockout NOD mice, manifested by a progressive locomotor disability first affecting the front paws as observed by catwalk analysis, and a decrease in grip test performance. The pathology remains limited to peripheral nerve and striated muscle. The muscle disease is characterized by myofiber necrosis/regeneration and an inflammatory infiltrate composed of CD4+T-cells, CD8+T-cells and myeloid cells, resembling human myositis. Autoimmune neuromyopathy can be transferred to NOD.scid recipients by CD4+ but not by CD8+T-cells isolated from 40-week-old female ICOSL-/-NOD mice. The predominant role of CD4+T-cells is further demonstrated by the observation that neuromyopathy does not develop in CIITA-/-ICOSL-/-NOD in contrast to β2microglobulin-/-ICOSL-/-NOD mice. Also, the cytokine profile of CD4+T-cells infiltrating muscle and nerve of ICOSL-/-NOD mice is biased toward a Th1 pattern. Finally, adoptive transfer experiments show that diabetes development requires expression of ICOSL, in contrast to neuromyopathy. Altogether, the deviation of autoimmunity from the pancreas to skeletal muscles in the absence of ICOS/ICOSL signaling in NOD mice is strictly dependent on CD4+T-cells, leads to myofiber necrosis and regeneration. It provides the first mouse model of spontaneous autoimmune myopathy akin to human myositis.